The impact of bilateral anodal transcranial direct current stimulation of the premotor and cerebellar cortices on physiological and performance parameters of gymnastic athletes: a randomized, cross-over, sham-controlled study - Sajjad Anoushiravani; Jaber Alizadehgoradel; Asgar Iranpour; Omid Yousefi Bilehsavar; Asghar Pouresmali; Michael A. Nitsche; Mohammad Ali Salehinejad; Mohsen Mosayebi-Samani; Maryam Zoghi (Scientific Reports, 2023)
Abstract Professional sports performance relies critically on the interaction between the brain and muscles during movement. Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique which modulates cortical excitability and can be used to improve motor performance in athletes. The present study aimed to investigate the effect of bilateral anodal tDCS (2 mA, 20 min) over the premotor cortex or cerebellum on motor and physiological functions and peak performance of professional gymnastics athletes. Seventeen professional gymnastics athletes participated in a randomized, sham-controlled, crossover study. In this study, we assessed the efficacy of two anodal tDCS protocols (2 mA, 20 min) with stimulation over the bilateral premotor cortex or cerebellum with the return electrodes placed over the opposite supraorbital areas. Power speed, strength coordination, endurance, static and dynamic strength, static and dynamic flexibility, and rating of perceived exertion were measured before and immediately after tDCS interventions (bilateral anodal tDCS over premotor cortices, anodal tDCS over the cerebellum, and sham tDCS). Additionally, physiological muscle performance parameters, including maximum voluntary isometric contraction (MVIC) of upper body muscles, were assessed during tDCS. Bilateral anodal tDCS over the premotor cortex, compared to anodal tDCS over the cerebellum and sham tDCS conditions, significantly improved power speed, strength coordination, and static and dynamic strength variables of professional gymnastics athletes. Furthermore, bilateral anodal tDCS over the cerebellum, compared to sham tDCS, significantly improved strength coordination. Moreover, bilateral premotor anodal tDCS significantly increased MVIC of all upper body muscles during stimulation, while anodal tDCS over the cerebellum increased MVIC in only some muscles. Bilateral anodal tDCS over the premotor cortex, and to a minor degree over the cerebellum, might be suited to improve some aspects of motor and physiological functions and peak performance levels of professional gymnastics athletes. Clinical Trial Registration ID: IRCT20180724040579N2.